A phytochemical and pharmacognostic approach of Ficus hispida Linn: a review - Choudhury, Asif; Jha, Deepak Kumar; Rajashekhar, U. (International Journal of Basic & Clinical Pharmacology, 2021)
Herbal plants are arguably poised for a comeback as like sources of ethnic health products in the main due after their vast desire in accordance with synthesize complicated combinations on structurally diverse compounds, which ought to furnish a safer than more holistic approach in conformity with disease cure and prevention. Ficus hispida (FH) Linn belonging to the family Moraceae, who have various pharmacognostic properties. The class Ficus constitutes a necessary crew on trees, now not solely concerning their extensive medicinal virtue however also of their growth habits yet religious significance. Almost every part over those plants is ancient as a traditional belief on treatment because of the treatment on a variety of ailments through Indian traditional healers. The goal on the existing instruction is to accumulate competencies over ethno-medicinal and pharmacognostic importance about FH. FH includes extensive sorts on bioactives compounds as alkaloids, proteins and amino acids, carbohydrates, flavonoids, sterols, phenols, glycosides, gums and mucilage, saponins and terpenes. Multiple scientific researches have been published to establish the scientific foundation over common medicinal values attributed in conformity with FH of terms on ayurvedic usage the plant for blood disorders, anemia, dysentery, hemorrhoids, stomatorrhagia, jaundice and ulcers. The crop fruits are used namely aphrodisiac, lactagogue, emetic and tonic. Furthermore, pharmacological activities like anticancer, antioxidant, hepatoprotective, cardioprotective, anti-inflammatory have been additionally acknowledged recently. Till now, no action has been published in conformity with elaborate the pharmacognostic functions of FH Linn. The existing decrial is, therefore, an endeavour to relinquish a clear estimate of its pharmacognosy and phytochemistry and a considerable survey over its pharmacological activities.